Grid integration of renewable energy: A systematic review bridging techno-economic optimization and smart grid architectures - Prawiraharjo, Bagus Satrio Utomo; Rizky Adi Nugraha; A. Fajrin K. Wijaya; Bonifacius Raditya Yudha (JTTM : Jurnal Terapan Teknik Mesin, 2026)
The escalating penetration of renewable energy (RE) sources necessitates addressing interconnected technical barriers across stability, power quality, and intelligent governance. This study presents a systematic literature review (SLR) of Google Scholar, IEEE Xplore, Scopus, and ScienceDirect databases (2018–2024) to synthesize critical challenges in large-scale RE integration. Diverging from existing reviews that isolate technical domains, this work adopts a holistic framework connecting frequency stability, power quality (PQ) disturbances, techno-economic optimization, and smart grid architectures. Key findings reveal that inverter-based resources (IBR) induce critical inertia deficits and harmonic distortions, requiring hybrid mitigation strategies combining Battery Energy Storage Systems (BESS) with Synchronous Condensers (SC). Moreover, prevalent simulation tools exhibit significant seasonal deviations (RMSE >30%), underscoring the absence of localized calibration protocols. The analysis identifies substantial research gaps in standardized PQ metrics for DC microgrids, real-time adaptive protection systems, and cybersecurity frameworks for prosumer ecosystems. This review contributes a comprehensive taxonomy of integration barriers and delineates future trajectories toward resilient, data-driven power systems.